Suggesting a sports training program using cardio exercises to reduce fat percentage and improve body image for obese women (20-30) years - Guesmi, Abdelmalek; Cheriet, Houssem eddine (Journal of Human Sciences, 2021)
Our study aimed to know the effect of the proposed sports program using cardio exercises in reducing the percentage of fat and improving the body image of obese women, in order to find out the extent of effectiveness, we applied the experimental method to a purposeful sample according to their excess weight, which consisted of 30 women divided equally (15) in the experimental sample (15) in the control sample. The results indicated that there were statistically significant differences in favor of the dimensional measurements of the experimental sample, which means that the proposed training program had an effect on reducing the percentage of fat and improving the body image of obese women from 20 to 30 years old.